Endoscopic management of postoperative upper gastrointestinal leakage - Ji Yong Ahn (Society of Gastrointestinal Intervention, 2022)
Anastomotic leakage is a potentially life-threatening adverse event that can occur after gastrectomy or gastric bypass surgery, ranging in severity from minor anastomotic defects to fulminant cases. The management of anastomotic leakage varies according to the time of diagnosis and the severity of the leakage; therefore, some cases can be managed conservatively, while others require urgent exploration. Despite aggressive medical and/or surgical management, some patients develop sepsis with multiple organ failure, leading to death. Hence, the management of anastomotic leakage imposes a significant burden on hospital resources. Due to the poor success rate of conservative therapy, anastomotic leakage management is usually performed surgically, which is associated with high morbidity and mortality. Given these concerns, non-operative treatment by endoscopic management, which uses sealants, hemoclips, self-expandable metal stents, and vacuum-assisted sponge closure, may be a valid alternative modality. According to recent studies, the results of endoscopic management for postoperative leakage have improved due to developments in instruments. Therefore, endoscopic management can be considered as an appropriate treatment option for properly selected patients with postoperative leakage.